Localization of Production Import Reduction and Industrial Policy - Abdumalikovich, Bektemirov Abdukhamid; Ergashjon oʻg‘li, Mardanov SHertoy; Karim qizi, Umurzoqova Sevinch (Journal of Innovation in Education and Social Research, 2024)
The article focuses on the need to fill the domestic market with necessary consumer goods and deepen the level of localization by expanding the production of import-substituting products from local raw materials based on industrial cooperation.